Perspectives on Treating Outer Space as a Resource Within Ecological Economics: An Analysis of the Space for V4 Project - Majewska, Julia (Publishing House of Wroclaw University of Economics and Business, 2025)
Outer space is increasingly playing a pivotal role in the economic development of Earth, despite remaining insufficiently regulated from a legal perspective and largely overlooked within mainstream economic theory. This paper aimed to enrich the field of ecological economics by conceptualising outer space as a distinct type of resource, encompassing both extraterrestrial material assets and space itself as an intangible, multidimensional resource. The study employed a systematic literature review and a case study approach to examine the contribution of outer space to sustainable development on Earth. Particular emphasis was placed on the importance of the Earth’s orbits, arguing that outer space should be treated as a unique category of resource, not merely as a component of the natural environment but also a critical enabler of the Sustainable Development Goals (SDG).
Quote as: Majewska, J. (2025). Perspectives on Treating Outer Space as a Resource Within Ecological Economics: An Analysis of the Space for V4 Project. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 170-180). Publishing House of Wroclaw University of Economics and Business.
Keywords: outer space; ecological economics; sustainable development